Differentiate y = (x^2 + 3)^2

We have to use the chain rule here. If we set u to the inside of the bracket, u = x^2 + 3 and differentiating we get du/dx = 2x. Now the original expression becomes y = u^2. Differentiating this with respect to x, dy/dx = du/dx * dy/du using the chain rule. dy/du = 2u and du/dx is 2x so the final answer dy/dx = 2x*2(x^2 + 3) = 4x(x^2 + 3).

Answered by Matthew H. Maths tutor

6250 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the integral of (2(3x+2))/(3x^2+4x+9).


How do I differentiate y = ln(sin(3x))?


Given ∫4x^3+4e^2x+k intergrated between the bounds of 3 and 0 equals 2(46+e^6). Find k.


How do I deal with parametric equations? x = 4 cos ( t + pi/6), y = 2 sin t, Show that x + y = 2sqrt(3) cos t.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences